Subjective suffering in patients with low back pain - Pereira, Marta (2020)
Low back pain (LPB) is a prevalent rheumatic and musculoskeletal disease and patients often experience physical discomfort and functional limitations. This study aimed to evaluate how subjective suffering relates to illness perceptions, pain intensity and psychological morbidity as well as to understand the mediator (direct and indirect) effects on functional disability. Methods: A cross-sectional study with 125 patients who received physiotherapy and answered the following instruments: Illness Perception Questionnaire-Revised; Illness Subjective Suffering Inventory; Hospital Anxiety and Depression Scale and the Oswestry LBP Incapacity Questionnaire. Results: In the structural equation modeling analysis, subjective suffering totally mediated the relationship between both emotional response (estimate = 0.068, 95% highest posterior density interval [HPDI] = [0.017, 0.133]), consequences (estimate = 0.118, 95% HPDI = [0.035, 0.211]) and functional disability. The relationship between coherence and disability was partially mediated by subjective suffering (estimate = −0.067, 95% HPDI = [−0.134, −0.016]). Only identity and pain intensity showed direct effects on functional disability. Conclusion: Intervention in patients with LBP should focus on subjective suffering to reduce functional disability, providing information and promoting the acceptance of disease and pain.